Информационная технология идентификации дактилем украинского жестового языка - Бармак, А.В.; Касьянюк, В.С.; Шкильнюк, Д.В.; Крак, Ю.В. (Управляющие системы и машины, 2015)
Рассмотрены проблемы и методы разработки информационной технологии для идентификации знаков дактильной азбуки украинского жестового языка. Информационная технология базируется на результатах анализа информативности характеристических признаков, предложенных для распознавания. Технология распознавания учитывает требования воспроизведения жестовой речи людьми с различными размерами рук и на разных фокусных расстояниях. Розглянуто проблеми і методи розробки інформаційної технології для ідентифікації знаків дактильної абетки української жестової мови. Інформаційна технологія базується на результатах аналізу інформативності характеристичних ознак, запропонованих для розпізнавання. Технологія розпізнавання враховує вимоги відтворення жестового мовлення людьми з різними розмірами рук та на різних фокусних відстанях. Introduction. The problems of the multimedia systems development for sign language recognition as a means of communication between people with hearing disabilities, is very important. The creation of the tools that will ensure the equal conditions for communication, perception and mastery of information for deaf people in society is crucial. One of the current trends is the creation of information technology for recognition of dactyl sing language. Purpose. The aim of the research is to create an information technology for the Ukrainian sign language alphabet identification. Information technology should be based on an features analysis. Results. In the paper proposes the system of classification and identification dactyl alphabet of the Ukrainian sign language. Classification dactyl alphabet elements made by features that do not depend on the individual hands and focal length of the video recording, which helped to define classes and some dactylems that uniquely recognized on these features. The study shows that the effective characteristicfeatures are geometry-topological parameters of the man hand and the contour analysis descriptors. The advantages of the approach is to build a cascade classifier by which dactylems set is divided into separate subsets. To build a system of the objects recognition due to the several different classes, using the dichotomy principle. For each node of the tree of optimal band-separating classifier is synthesized according to the information about the objects contained in the training sequence. Conclusions. Information technology testing, conducted with the groups of people different age and sex parameters and different focal lengths, proved the unambiguous identification of the correct 80–87 %. The experimental group at a given correct display recognition shows 98 %.